Isolation and Characterization of Bacterial Pigments for Dye-Sensitized Solar Cell Applications - Diviana, Tan Robert (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Solar energy is the best known alternative to the current costly and environment polluting fossil fuel. There have been numerous reports on the use of natural pigments extracted from plants and fruits as sensitizer of these sunlight harvesting cells. However, the use of plants and fruits are impractical due to the high cost and low availability. Thus, this study aims to investigate the potential of bacterial pigments isolated from pigmented bacteria for DyeSensitized Solar Cell (DSSC) applications. Pigment-producing bacteria were isolated from two different environmental sources which are soil from local farm and a water lake. Red and purple bacteria isolates designated as SM and CV were identified using polymerase chain reaction (PCR) analysis and 16s rRNA sequencing. The 16s rRNA sequence of the SM and CV isolates shows 100% similarity to Serratia marcescens and 99% similarity to Chromobacterium violaceum respectively. The bacterial pigments were then extracted and characterized by using Fourier Transform Infrared (FTIR), UV-vis spectrophotometry and Nuclear Magnetic Resonance (NMR) analyses where the pigment from Serratia marcescens were identified as prodigiosin while pigment from Chromobacterium violaceum was identified as violacein. Dye sensitized solar cells (DSSCs) were fabricated using prodigiosin and violacein extracted as sensitizers. Performance of cell under light bulb illumination recorded was 0.68 W for prodigiosin and 0.72 W for violacein. Both prodigiosin and violacein isolated showed the promising potential for DSSC applications for clean sustainable energy source.